Phonon dynamics of Zr67Ni33 and Fe80B20 binary glassy alloys - Vora, Aditya M; Gandhi, Alkesh L (BIBECHANA, 2021)
Binary amorphous alloys are the primary bulk metallic glasses (BMGs). Two binary BMGs Zr67Ni33 and Fe80B20 have been studied in the present work using the pseudo- alloy-atom (PAA) model based on the pseudopotential theory. Some important thermodynamic properties like Debye temperature and elastic properties like elasticity moduli and Poisson’s ratio at room temperature are theoretically computed with the help of pseudopotential theory from the elastic limit of the phonon dispersion curves (PDCs). The collective dynamics of longitudinal and transverse phonon modes are investigated in terms of eigenfrequencies of the localized collective modes. The presently computed results are compared with the other such data including theoretically generated results from the molecular dynamics at different temperatures as available in the literature and an acceptable agreement is found. BIBECHANA 18 (1) (2021) 33-47